After Saddam : prewar planning and the occupation of Iraq - Bensahel, Nora, 1971- (Rand Corporation monograph series., 2008)
This monograph begins by examining prewar planning efforts or postwar Iraq, in order to establish what U.S. policymakers expected the postwar situation to look like and what their plans were for reconstruction. The monograph then examines the role of U.S. military forces after major combat officially ended on May 1, 2003; the analysis covers this period through the end of June 2004. Finally, the monograph examines civilian efforts at reconstruction after major combat ended, focusing on the activities of the Coalition Provisional Authority (CPA) and its efforts to rebuilding structures of governance, security forces, economic policy, and essential services prior to June 28, 2004, the day that the CPA dissolved and transferred authority to the Interim Iraqi Government. The authors conclude that the U.S. government was unprepared for the challenges of postwar Iraq for three reasons: a failure to challenge fundamental assumptions about postwar Iraq; ineffective interagency coordination; and the failure to assign responsibility and resources for providing security in the immediate aftermath of major combat operations.